Developments in control theory towards glocal control - Qiu, Li, 1961-; Hara, Shinji, 1952- (IET control engineering series, 2012)
Drawing upon a collection of research articles from celebrated authors in the field of control theory and its applications, this Festschrift honours the work of Professor Shinji Hara, and lays a solid foundation towards the 'glocal control' theory.